A survey on the interest of University of the Philippines College of Home Economics Bachelor of Science in Clothing Technology undergraduate students and graduates in masteral program for clothing technology - Sagun, Diane Pagdanganan; Elumba, Ma. Patricia S. (2008.)
This study sought to determine whether the graduates and undergraduates of the Bachelor of Science in Clothing Technology in the University of the Philippines, College of Home Economics (UP CHE BSCT) are interested in pursuing a masteral program in Clothing Technology. Normative survey method is the study's research design. Using convenience sampling, 22 graduates and 40 undergraduates of UP CHE BSCT were selected as respondents. The research resorted to convenience sampling because most of the BSCT graduates did not cooperate in the study. Descriptive statistics was used to interpret trends and directions given to the result of the study. The respondents' opinions and suggestions regarding the development and integration of the BSCT program were asked using a questionnaire and interviews. The BSCT undergraduates suggested and recommended courses and subjects that will strengthen and improve the BSCT program. Most of the suggested courses and subjects are commercial rather than technical. Majority of the respondents are interested in taking a masteral program for Clothing Technology, however, there are some respondents who are not interested because of their limitations of their regular work schedules and lack of funds for them to enroll in a masteral program. To improve the BSCT program today, it was suggested that more science and technology courses in the curriculum be added for greater knowledge and skills in the science and technology aspects of the course. The facilities also need improvement for students to practice application of the lectures and technology practices required in the course. This study will contribute to the development of the quality of education and enhance the BSCT curriculum in producing globally-competitive people for the clothing and textile industry.
Thesis (BSCT)--University of the Philippines Diliman
Keywords: Bachelor of Science in Clothing Technology--Graduates.; University of the Philippines Diliman. College of Home Economics -- Alumni